2016
DOI: 10.1140/epjc/s10052-016-4425-x
|View full text |Cite
|
Sign up to set email alerts
|

On the Faddeev–Jackiw symplectic framework for topologically massive gravity

Abstract: The dynamical structure of topologically massive gravity in the context of the Faddeev-Jackiw symplectic approach is studied. It is shown that this method allows us to avoid some ambiguities arising in the study of the gauge structure via the Dirac formalism. In particular, the complete set of constraints and the generators of the gauge symmetry of the theory are obtained straightforwardly via the zero modes of the symplectic matrix. In order to obtain the generalized Faddeev-Jackiw brackets and calculate the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…Hence, for s = 1 and the limit γ → ∞, we recover the Dirac canonical structure of Palatini's action [11]. It is important to remark that in the BL model the fields e, A and their canonical momenta have become noncommutative, while in Palatini's action they are commutative.…”
Section: Hamiltonian Dynamics For Three-dimensional Bl Gravitysupporting
confidence: 59%
See 2 more Smart Citations
“…Hence, for s = 1 and the limit γ → ∞, we recover the Dirac canonical structure of Palatini's action [11]. It is important to remark that in the BL model the fields e, A and their canonical momenta have become noncommutative, while in Palatini's action they are commutative.…”
Section: Hamiltonian Dynamics For Three-dimensional Bl Gravitysupporting
confidence: 59%
“…It is important to comment that our results are given in a general form and contain the cases for > 0 and < 0, thus in particular we can reproduce the results given in [17] where the case < 0 was studied. On the other hand, in the limit γ →∝ the action (31) is reduced to S CS (ω) and the Dirac brackets are reduced to those reported in [11], where Palatini's theory was analyzed. Finally, we can observe that in this section we have proved the equivalence between the BL model and the Chern-Simons theory, thus the standard quantization procedure can be performed.…”
Section: Relation With Chern-simons Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…There exists, however, a symplectic realization that provides straightforward effective tools for the study of the dynamical structure of Lagrangian field theories, which is geometrically well motivated and is based on the symplectic structure of the space-phase [55][56][57][58][59][60][61], and therefore it is different from Dirac's approach. The advantage of this construction is that we do not need to catalogue the constraints as first-and second-class ones.…”
Section: Jhep01(2021)089mentioning
confidence: 99%
“…[26] it has been shown that, though technically different, the Faddeev-Jackiw approach and Dirac method are physically equivalent. A recent application of Faddeev-Jackiw (F-J) formalism was discussed in [27], where topologically massive gravity was studied ( other interesting works can be found in references cited here).…”
Section: Introductionmentioning
confidence: 99%